(untitled) (Journal of Medicine, 2018)
Bullous systemic lupus erythematosus (BSLE) is extremely rare but distinct disease, characterized by vesicobullous skin eruptions in systemic lupus erythematosus (SLE). It can develop either before or after a diagnosis of SLE has been established. BSLE is characterized by a dermatitis herpetiformis-like histology and an autoimmunity to type VII collagen. It must be differentiated from other autoimmune vesicobullous diseases such as epidermolysis bullosa acquisita, dermatitis herpetiformis, linear IgA disease, and bullous pemphigoid. Its important to combine clinical, histological, and immunofluorescence findings to establish a diagnosis of BSLE. We report a case of BSLE to illustrate and emphasize the need for an integrative diagnostic approach. J MEDICINE JUL 2018; 19 (2) : 123-125